2007
DOI: 10.5688/aj710480
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoepidemiology Education in US Colleges and Schools of Pharmacy

Abstract: to examine the type and extent of pharmacoepidemiology education offered to professional (PharmD) and graduate (MS/PhD) students. Results. The response rate was 100%. Of the 89 schools surveyed, 69 (78%) provided pharmacoepidemiology education to their professional students. A mean of 119 (660) PharmD students per college/ school per year received some pharmacoepidemiology education (range 1-60 classroom hours; median 10 hours). Thirty-five schools (39%) provided education to a mean of 6 (65) graduate students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…This study shows that 51/151 (33.7%) of the included schools have provided pharmacoepidemiology education, which is a much lower number compared to the 74/89 schools (83%) from the survey conducted in 2007 in US. [33] Several studies have reported on the importance of the pharmacoepidemiology discipline and that it be integrated into an important analysis of information concerning areas such as ADRs and post-marketing surveillance research. In addition, conducting research will be one of the main roles for pharmacists working in research units or departments in hospitals or other institutions, such as pharmaceutical companies and regulatory authorities.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that 51/151 (33.7%) of the included schools have provided pharmacoepidemiology education, which is a much lower number compared to the 74/89 schools (83%) from the survey conducted in 2007 in US. [33] Several studies have reported on the importance of the pharmacoepidemiology discipline and that it be integrated into an important analysis of information concerning areas such as ADRs and post-marketing surveillance research. In addition, conducting research will be one of the main roles for pharmacists working in research units or departments in hospitals or other institutions, such as pharmaceutical companies and regulatory authorities.…”
Section: Discussionmentioning
confidence: 99%
“…As the profession transitions to a more patient-centered profession, the importance of ESAP content at schools and colleges of pharmacy in the United States will likely increase (Nwokeji et al, 2005;Nwokeji et al, 2007). Both the educational backgrounds of ESAP faculty and the content taught within the discipline vary greatly.…”
Section: Resultsmentioning
confidence: 99%
“…Questionnaire items were developed from a thorough review of variables and factors used in previous studies and previous survey instruments used to assess pharmacoepidemiology and pharmacoeconomic education being though in US pharmacy programs [3,16,[20][21][22][23][24]. The final questionnaire comprised of 5 sections.…”
Section: Questionnaire Development and Validationmentioning
confidence: 99%